2016
DOI: 10.1590/1678-775720150324
|View full text |Cite
|
Sign up to set email alerts
|

The effect of swimming on oral health status: competitive versus non-competitive athletes

Abstract: Young swimmers are particularly susceptible to the onset of oral diseases. Objective To evaluate the oral health status in young competitive and non-competitive swimmers, involving an assessment of salivary cariogenic bacteria and secretory IgA (S-IgA) concentration.Material and Methods Before training sessions (T1), 54 competitive and 69 non-competitive swimmers had the following parameters assessed: decayed, missing, and filled teeth (DMFT), Plaque Index (PlI), and Gingival Index (GI). At T1 and after traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
2
29
1
4
Order By: Relevance
“…Many of the articles showed an increase in performance in using sports and energy drinks, even though they had deleterious effects on the athlete's health …”
Section: What Is Known About Sports Drinks and Nutrition?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the articles showed an increase in performance in using sports and energy drinks, even though they had deleterious effects on the athlete's health …”
Section: What Is Known About Sports Drinks and Nutrition?mentioning
confidence: 99%
“…Many of the articles showed an increase in performance in using sports and energy drinks, even though they had deleterious effects on the athlete's health. [64][65][66][67][68][69][70][71][72][73][74][75][76] One article specifically stated that because of the stimulant content within the sports and energy drink, they would not be appropriate for children and adolescents. This intake can lead to excessive caloric consumption and an increased risk of overweight and obesity as well as dental erosion.…”
Section: What Is Known About Sports Drinks and Nutrition?mentioning
confidence: 99%
“…The present study demonstrated that electromyographic analysis, cardiopulmonary test associated with previously reported tests as microbial markers, immune status and sporting characteristics [21] were important for establishing guidelines for management of training load in order to minimize physical stress and the risk of oral infection.…”
Section: Discussionmentioning
confidence: 65%
“…Some studies have reported the adverse effects of periodontal and dental diseases on athletic performance. A relationship has been found between the performance of swimmers and the decay of teeth even if the relationship is weak (18). High caries score and periodontal disease negatively affect performance and may be associated with athlete muscle, tendon, and bone injuries (19).…”
Section: Introductionmentioning
confidence: 99%